Систематична структура урбанофлори Чернігова - Зав’ялова, Л.В. (Український ботанічний журнал, 2010)
Установлен видовой состав урбанофлоры Чернигова (1050 видов из 470 родов и 115 семейств), представлены анализ систематической структуры урбанофлоры Чернигова и результаты сравнения её главных пропорций и таксономических спектров с другими урбанофлорами (Брянска, Кривого Рога, Кировограда, Херсона, Николаева, Симферополя, Ужгорода, Малого Полесья) и флорой Восточного Полесья. Установлено, что урбанофлора Чернигова является бореальной и сохраняет зональные черты. По структуре таксономических спектров и основным соотношениям исследованная флора наиболее близка к урбанофлоре Брянска и флоре Восточного Полесья. The species composition is established for the Chernihiv urban flora, which contains 1050 species belonging to 470 genera and 115 families. An analysis of its taxonomic structure is given, as well as the results of comparison of its main proportions and taxonomic spectra with other urban floras (such as Bryansk, Kryvyi Rig, Kirovograd, Kherson, Mykolaiv, Simferopol, Uzhgorod, and urban floras of Male Polissya) and the flora of Eastern Polissya. It is demonstrated that the Chernihiv urban flora is boreal and retain zonal floristic features. By the structure of taxonomic spectra and basic main proportions of floral elements, the studied flora is most similar to the urban flora of Bryansk and the flora of Eastern Polissya in general.